Recent changes in British wage inequality: Evidence from firms and occupations - Schäfer, Daniel; Singleton, Carl (Edinburgh, 2017)
"Using a dataset covering a large sample of employees and their mostly very large employers, we study the dynamics of British wage inequality over the past two decades. Contrary to other studies, we find little evidence that recent increases in inequality have been driven by differences in the average wages paid by firms. Instead greater dispersion within firms can account for the majority of changes to the wage distribution. After controlling for the changing occupational content of employee wages, the role of average firm residual differences is approximately zero; the modestly increasing trend in between-firm wage inequality is explained by a combination of changes in between-occupation inequality and the occupational specialisation of firms. It is possible that previous studies, which assign some of the importance of changes in the between-firm component to industry, have misrepresented a significant role for occupations. These results are robust across measures of hourly, weekly and annual wages."